Influence of Beta-glucanase Supplementation on Growth Performances and Digestive Organs Weights of Broiler Chickens Fed Corn, Wheat and Barley-based Diet - Mathlouthi, N.; Ballet, N.; Larbier, M. (International Journal of Poultry Science, 2011)
This study was performed with broiler chickens to evaluate the effects of adding beta-glucanase on bird performances and digestive organs weights. A total of 1600 1-day-old broilers (Arbor Acres) were divided into 2 groups and fed either a control diet (group C) based on corn, wheat and barley or a control diet supplemented with beta-glucanase preparation (Safizym GP 40, Lesaffre Feed Additives, France) at the dose of 40 mg per kg of diet (group G). Body weight, feed intake were recorded at 40 days of age. The same day, 8 chickens from each group were slaughtered for carcass yield and digestive organs weights. Experimental data were statistically analyzed by using the ANOVA procedure of Stat View programme. Throughout the whole trial period (1-40 days of age), body weight was significantly (p